2012
DOI: 10.1186/1752-153x-6-146
|View full text |Cite
|
Sign up to set email alerts
|

Reverse phase chromatographic behaviour of major components in Capsicum Annuumextract

Abstract: BackgroundThe purpose of the study is to develop a suitable analytical method in order to establish appropriate conditions for isolation and assay of the dominant compounds in extracts of Capsicum annuum.ResultsThe studies are performed with standard substances to establish the HPLC conditions for complete separation of capsaicin and dihydrocapsaicin, the two major components of interest. Because of their prevalent apolar features, reverse phase chromatographic version was approached. Systematic studies on dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…In order to determine the concentration of essential elements from the studied samples, the atomic absorption method was used (Contra 300), Analytik Jena [25,26]. The component parts of the variants used in the study were dried in a drying oven at 105°C, and then there was measured between 0.5 and 1 g per each sample, and finally they were subjected to a process of disaggregation (digestive or mineralization) for bringing them into solution [27,28].…”
Section: Determination Of Macroelements and Microelementsmentioning
confidence: 99%
“…In order to determine the concentration of essential elements from the studied samples, the atomic absorption method was used (Contra 300), Analytik Jena [25,26]. The component parts of the variants used in the study were dried in a drying oven at 105°C, and then there was measured between 0.5 and 1 g per each sample, and finally they were subjected to a process of disaggregation (digestive or mineralization) for bringing them into solution [27,28].…”
Section: Determination Of Macroelements and Microelementsmentioning
confidence: 99%
“…Hecht and collab. had reported that the main impediments in the spread of catfish fingerlings are the cost of synthetic hormones although wild fry and fingerlings may be collected HECHT et al, 1996;BUTNARIU et al, 2012 , but are not sufficient for a viable stocking programme.…”
Section: Introductionmentioning
confidence: 99%
“…Primary and collateral plant metabolites with pharmacodynamic action or used in food industry have some common characteristics: most of them are non-protein chemical compounds that can be extracted from plant material by steam distillation, with organic solvents or aqueous and are low molecular weight compounds excluding biopolymers [4], condensed tannins and some polysaccharides such as gums, pectin and starch [5]. Vegetables that can be used in treatment or control certain diseases are as follows: -Cold: carrot, celery, onion and spinach [6,7].…”
Section: Vegetables and Pharmacodynamic Compoundsmentioning
confidence: 99%